Finance / Zvi Bodie, Robert C. Merton. - Bodie, Zvi (Prentice Hall, 2000)
This introduction to finance has a broad scope, placing an emphasis on general principles within the field. It builds its presentation upon the three 'pillars' of finance: optimization over time, asset valuation and risk management